The impact of ethical governance on digital leadership effectiveness and operational efficiency in South African banks: Perspectives from Digital Leaders, Managers, and Employees - Balkissoon, Rishal (University of Pretoria, 2026)
Mini Dissertation (MBA)--University of Pretoria, 2025.